2020
DOI: 10.1088/1361-648x/abace3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a new interatomic potential to investigate the thermodynamic properties of hypo-stoichiometric mixed oxide fuel U1−y Pu y O2−x

Abstract: The behaviour of stoichiometric U1-yPuyO2 compounds used as nuclear fuel is relatively well understood. Conversely, the effects of stoichiometry deviation on fuel performance and fuel stability are intricate and poorly studied. In order to investigate what affect these have on the thermophysical properties of hypo-stoichiometric U1-yPuyO2-x mixed oxide fuel, new interaction parameters based on the many-body CRG (Cooper-Rushton-Grimes) potential formalism were optimized. The new potential has been fitted to mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…(44c), the thermal conductivity k and the heat capacity C p depend on temperature but also on the phase composition and the oxygen content. In fuel performance codes, the heat capacity is often calculated according to empirical correlations or given by laws resulting from atomic-scale simulations [53,54,55]. It is interesting to keep in mind that C p could be calculated at run-time with a thermochemical solver coupled with a CALPHAD database such as, for instance, OpenCalphad with the TAF-ID.…”
Section: Reduction To the Uranium-oxygen Binary System In A Solid/liq...mentioning
confidence: 99%
“…(44c), the thermal conductivity k and the heat capacity C p depend on temperature but also on the phase composition and the oxygen content. In fuel performance codes, the heat capacity is often calculated according to empirical correlations or given by laws resulting from atomic-scale simulations [53,54,55]. It is interesting to keep in mind that C p could be calculated at run-time with a thermochemical solver coupled with a CALPHAD database such as, for instance, OpenCalphad with the TAF-ID.…”
Section: Reduction To the Uranium-oxygen Binary System In A Solid/liq...mentioning
confidence: 99%
“…Mixed (U, Zr)O 2 oxides compositions were generated by randomly substituting U with Zr on cation sites in a F m 3m cubic uorite structure; no specic random structuregeneration procedure such as SQS (special quasirandom structures) was used, as recent work proved it had little to no impact for determining density or heat capacity in large cells for mixed oxides systems [14]. A single purely random conguration was used for each composition, as previous work from Cooper et al showed only small variations between multiple random congurations above 2500 atoms [10].…”
Section: Computational Details 231 Simulation Parametersmentioning
confidence: 99%
“…Covalent bond distances from the Morse and Buckingham part (ρ, r 0 ) are tted rst because of their important sensitivity: ensuring their minimization is key to avoid artefacts later in the tting run simulations; A αβ and D αβ are tted next. Finally, EAM parameters (G α , n β ) are tted last, since they bear no physical meaning relative to the system, and only serve to adjust the collective behaviour in the cell [14].…”
Section: Fitting Strategymentioning
confidence: 99%